University education: a potential health promotion intervention for Australian baby boomers. Issue 6 (2nd November 2019) - Hardy, Margaret; Summers, Mathew; Millear, Prudence; Oprescu, Florin
ABSTRACT: It is forecast that ageing baby boomers will have a substantial impact on future health expenditure. The primary aim of this study is to explore the perceived health benefits of later life university study for baby boomers. An online survey of Australian baby boomers examined their beliefs regarding the health benefits of studying at university in later life and related barriers. Data from 261 respondents revealed the main benefits to be gained from later life university study were improved critical thinking and decision-making skills. The main motivators were personal fulfilment and mental or intellectual stimulation, and financial cost the most important barrier. The results from this study suggest that university study in later life should be considered as a health promotion intervention for older adults seeking mental/intellectual stimulation. Enhancement of cognitive function through such interventions may have significant positive impacts on health outcomes across short, medium and long-term timeframes.